The Effect of Emotional Maturity on Self Harm Behavior in Adolescent - Sandjaja, Stefanus Soejanto; Aliffia, Natasya (JITSS (Journal of Innovation and Trend in Social Sciences), 2025)
The increasing prevalence of self-harm behavior among adolescents presents a serious concern for schools and mental health practitioners, creating an urgent demand for research that explores underlying psychological determinants, including the role of emotional maturity in shaping students' coping responses to emotional distress. The purpose of this study was to examine the relationship between emotional maturity and self-harm behavior among tenth and eleventh-grade adolescents at SMK Negeri 16 Jakarta. This study employed a quantitative correlational design using a survey approach. Emotional maturity and self-harm behavior were measured using Likert-scale questionnaires. A total of 108 students from three classes participated in the study. The data were analyzed using simple linear regression. The results showed a significant relationship between emotional maturity and self-harm behavior. These findings indicate that higher emotional maturity is associated with a lower likelihood of self-harm behavior among students at SMK Negeri 16 Jakarta.